The concept of environmental damage in the Qur'an: An analysis of the thematic method of Abdussatar Fathullah Sa'id and its relevance to Hifzhul Bi'ah - Rohmatulloh, Acep Ihsan (UIN Sunan Gunung Djati Bandung, 2025)
Environmental degradation results from humans disobeying God's command to maintain harmony with nature. All elements of the universe reflect God's word and form an ecosystem. When humans disrupt this balance through selfish actions, nature reacts in ways harmful to human life, underlining that everything is subject to Allah's will. This study analyzes the concept of environmental damage in the Qur'an using Abdussatar Fathullah Said's maudu’i method and explores its connection with Yusuf Qardawi's idea of hifzhul bi'ah (environmental preservation). Using qualitative library research, it finds that the Qur'an's teachings on preventing environmental harm align with hifzhul bi'ah: 1) Humans, as earth's caliphs, must preserve and protect nature (QS Al-Baqarah 2:30); 2) The Qur'an commands maintaining and forbids destroying the environment, as in QS Al-A'raf 7:56 and other verses (QS Al-Baqarah 2:11-12, 60, 205; Al-A'raf 7:56, 74, 85; Hud 11:85; As-Syu'ara 26:150-152).